Applying Green Social Work in Program Keluarga Harapan: Towards Sustainable Family Food Security - Pristhalia Vernanda Gunawan; Gina Indah Permata Nastia (LP2M Universitas Sarjanawiyata Tamansiswa, 2026)
The Green Social Work (GSW) approach is a social work approach that integrates environmental and social issues. This trend offers solutions to address the challenges of poverty and environmental crises simultaneously. PKH is one of the government's flagship programs in eradicating poverty, combined with increasing the capacity of PKH Beneficiary Families (KPM) through local economic empowerment, which has begun to promote the environmental concept as a solution to increase family food security. This study aims to analyze the implementation of the GSW approach in the practice of PKH assistance and its contribution to family food security in Dlanggu District, Mojokerto Regency. This study used a qualitative descriptive method. The results showed that the majority of assistance activities have focused on environmentally based activities such as utilizing gardens or empty yards to grow various types of vegetables, managing recycled waste to make compost, and family farming education. These activities encourage increased family food availability and awareness of the importance of environmental sustainability. However, the implementation of GSW in PKH assistance still faces several challenges, including limited capacity of PKH assistants, lack of participation of KPM PKH, and less than optimal awareness of KPM PKH regarding the utilization and management of local food resources. Therefore, strengthening the capacity of PKH assistants, cross-sector collaboration, and increasing the knowledge and skills of KPM PKH regarding family food security are key to the successful implementation of GSW in PKH assistance practices.